Generating academic standards in planning practice education : final report to the Australian Learning and Teaching Council. - Jones, Martyn; Jackson, John; Coiacetto, Eddo; Budge, Trevor; Coote, Matthew; Steele, Wendy; Gall, Sarah; Kennedy, Melissa ([Australian Learning and Teaching Council], 2009)
This project investigates understanding of academic standards within the discipline of urban and regional planning. It focuses on standards, assessment practices and student outcomes in planning practice education. The project affirms the value afforded by planning programs to preparing students for professional practice. Those involved in structured work placements - educators, practitioners and students - strongly endorse this form of practice education in undergraduate programs. The project shows how practice is rendered a legitimate part of academic endeavour. The quality of the student practice learning experience is very much affected by the ways in which their planning programs bridge the worlds of work and academia. The project develops a set of guiding principles for enhancing assessment practices and academic standards for structured work placement. [Executive summary, ed]